Role of Granulosa Cell Dysfunction in Women Infertility Associated with Polycystic Ovary Syndrome and Obesity - Stéphanie Chauvin (Biomolecules)
Infertility affects 17.5% of couples worldwide, and is notably caused in females by ovarian disorders that impact follicle development and oocyte maturation. Polycystic ovary syndrome (PCOS), affecting 8 to 13% of women of reproductive age, is a leading cause of anovulation and is characterized by arrested antral follicle development before the preovulatory stage. Reproductive issues of PCOS are often exacerbated in overweight or obese women. Obesity, which is increasingly prevalent worldwide, is also associated with anovulation, primarily due to defects in oocyte quality. Oocyte quality and competence depend on the proper activity of granulosa cells (GCs), which surround and support the oocyte. GCs produce key factors, such as 17β-estradiol, which regulate follicle growth and oocyte maturation. They also provide essential metabolic support for oocyte maturation and play a critical role in ovulation and fertilization. This review outlines the physiological role of GCs in follicle growth and maturation and explores recent advancements in understanding GCs’ molecular and physiological dysfunctions that contribute to infertility in PCOS and obesity. Improved knowledge of the endocrine mechanisms underlying follicular abnormalities in these conditions could help to predict oocyte competence and enhance assisted reproduction outcomes.